An investigation of a varying G through Strong Lensing and SNe Ia observations - R.F.L. Holanda; Marcelo Ferreira; Javier E. Gonzalez (Physics Letters B)
In this paper, we analyze the potential variation of the gravitational constant G using data from strong gravitational lensing systems and Type Ia supernovae. Testing G(z) parameterizations where G(z)=G0(1+G1z) and G(z)=G0(1+z)G1, we also account for the influence of G on the luminosity of SNe Ia through the Chandrasekhar mass-luminosity relation. Only the flat universe hypothesis is considered. Constraints from 158 lensing systems and the Pantheon+ sample show no significant evidence of G variation. However, although the results are compatible with no variation, the errors are not yet sufficiently restrictive to rule out any variation of G with high statistical confidence. This study highlights the viability of using combined astrophysical data to probe variations in fundamental constants, suggesting that future surveys could refine these constraints.